Periodization and Party System Institutionalization in Latin America: A Reply to Mainwaring. Issue 3 (3rd April 2017) - Roberts, Kenneth M.
Abstract : The study of party system institutionalization in Latin America is complicated by the fact that political development in the region has been indelibly marked by period-specific stages and challenges of capitalist development. These periods are associated with distinct patterns of social mobilization, class conflict and political incorporation or exclusion of labour and popular constituencies. These patterns heavily condition the programmatic structuring of partisan competition and its impact on party system institutionalization. Important theoretical insights can be derived from the study of intra-regional variation in period-specific challenges and effects, but this requires careful attention to the factors that differentiate cases.